African sovereign wealth and pension funds summit report : formalising domestic African capital as a tool to leverage global institutional capital (Africa Investor GautengZA, 2014)
Shares the vision of the potential of the private sector to boost investments and create jobs with the ultimate goal of boosting economic growth on the African continent.
Keywords: INVESTMENT